STRATEGI PENGEMBANGAN OBJEK WISATA PANTAI GELORA SEBAGAI DESTINASI WISATA UNGGULAN DI KABUPATEN SUMBAWA - Wiwiek Igusnarti; Ika Fitriyani (Jurnal Ekonomi & Bisnis, 2025)
This study aims to formulate a strategy for developing the Gelora Beach Tourist Attraction as a leading tourist destinations in Sumbawa District. The type of this study was descriptive with a qualitative approach. The type of data used in this study was qualitative data in the form of informants' answers obtained directly through interviews. The informants in this study consisted of village heads and managers of the Gelora Beach Tourist Attraction. The interview technique used was an open interview, where respondents were asked to explain conditions related to the strengths, weaknesses, opportunities and threats that exist at the Gelora Beach Tourist Attraction. The data analysis technique was carried out using the SWOT analysis method. Based on the results of the internal and external factors analysis, 10 strategic alternatives were obtained that can be implemented in developing the Gelora Beach Tourist Attraction into a leading tourist destination in Sumbawa District, by supporting aggressive policies (growth-oriented strategies). The three main strategies that are prioritized in developing the Gelora Beach Tourist Attraction into a leading tourist destination are holding socialization of Sapta Pesona or raising awareness of the benefits of tourism for all levels of society in a sustainable and systematic manner; community-based tourism development; and human resources managing the Gelora Beach tourist attraction must have tourism certification.